Syntactic Scope and Interpretive Ambiguity in Normative Texts (A Case Study of the Tax Code) - Dilrabo Elova Qudratillayevna (Researchparks Publishing, 2026)
This article examines how a linguistic-logical approach can be used in the analysis of legal texts, based on Articles 370-377 of the Tax Code of the Republic of Uzbekistan. The study focuses on the sentence structure, syntactic scope, internal textual links, and practical interpretation of the rules related to individual income tax. The analysis uses semantic, propositional, pragmatic, and counterfactual methods. The results show that some provisions may lead to different interpretations because of open categories, reference words, the scope of conjunctions, and implicit semantic grounds. The article presents the linguistic-logical approach not as a replacement for linguistic expertise, but as an integrated way of examining the logical and pragmatic aspects of a normative text more deeply.